Chinese fossil vertebrates - Lucas, Spencer G. (Columbia University Press, 2001)
This book is a comprehensive, chronologically ordered review of China's vertebrate fossil record. It also presents a history of vertebrate paleontological studies in China and an entrée to some important issues of systematics, evolutionary history, paleoecology, taphonomy, and functional anatomy best elucidated by China's fossils.